The Attempt to Fulfill Restitution for Victims of Domestic Abandonment Crimes - Lubis, Syafrina; Agustanti, Rosalia Dika (Magister Hukum Universitas Semarang, 2024)
This article aims to analyze the legal protection for victims of domestic abandonment through restitution fulfillment. It is because imprisonment in the case of domestic abandonment basically cannot accommodate the economic losses suffered by the victims. Legal protection for victims should also focus on restoring the economic losses incurred during the abandonment. Therefore, the urgency of this article is the attempt to fulfill restitution for victims as the manifestation of the victim’s right. This article is normative legal research. The novelty of this article is about the attempt to fulfill restitution, which is studied based on positive law in Indonesia and the problems were analyzed using Gustav Radburch's legal theory on the principle of priority in three legal objectives. The research results indicate that one of the challenges of restitution fulfillment in the current legal system is when the victims are not submitting the restitution request before or even after a court verdict. Hence, the judges in their verdict cannot accommodate this restitution for the victims and they cannot receive their rights of restitution. Because of that it is expected that the attempt of restitution fulfillment will accommodate the economic losses suffered by victims during abandonment.